Las políticas de mundialización de la educación en Argentina y Colombia - Gabriela Portilla, Mónica (Universidad Santiago de Cali, 2020)
The purpose of this chapter is to describe and analyze the most relevant antecedents about the world order, its evolution over time and influence in higher education, from a historical perspective, in order to make known its beginnings and the conceptual plot in which it the arguments. I face the main transformations since the postwar period and the problems with the education system in Latin America, specifically with Argentina and Colombia. This chapter has to do with the cession of autonomy and independence of the National States in the design and implementation of their educational policies in particular, taking as a theoretical reference the thesis of "institutional isomorphism" or "homologies" that the countries adopt in a rational way and the institutions, presenting different degrees of intensity, correspondence and appropriation, as part of the international and territorial insertion of countries in globalization, configuring a new field of knowledge: the "supranational educational policy".